Evaluating the Frequencies of CNOT3, GRIA1, NFATC2, and PNPLA3 Variant Alleles and Their Association with L-Asparaginase Hypersensitivity in Pediatric Acute Lymphoblastic Leukemia in Addis Ababa, Ethiopia - Ali AM; Adam H; Hailu D; Howe R; Abula T; Coenen MJH (The Application of Clinical Genetics, 2023)
Awol Mekonnen Ali,1 Haileyesus Adam,2 Daniel Hailu,2 Rawleigh Howe,3 Teferra Abula,1 Marieke JH Coenen4 1Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Pediatrics and Child Health, School of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 3Armauer Hansen Research Institute, Addis Ababa, Ethiopia; 4Department of Human Genetics, Radboud Institute for Health Sciences, Radboud University Medical Center, Nijmegen, the NetherlandsCorrespondence: Awol Mekonnen Ali, Addis Ababa, Ethiopia, Tel +251 913914432, Email awolalim@gmail.comIntroduction: L-asparaginase is a vital component for the treatment of childhood acute lymphoblastic leukemia (ALL); however, hypersensitivity reactions and hepatotoxicity hinder its anti-neoplastic efficacy. Previous reports indicated that genetic variants in CNOT3, GRIA1, and NFATC2 genes might be associated with hypersensitivity reactions and PNPLA3 with liver function.Objective: In this study, it was investigated whether this association also exists in a pediatric ALL cohort from Ethiopia.Methods: Three variants GRIA1 rs4958351, CNOT3 rs73062673, and NFATC2 rs6021191 were genotyped in a cohort of 160 patients. Association analysis to investigate the association with hypersensitivity reactions was performed using logistic regression analyses. Besides these variants, a variant in PNPLA3 (rs738409) was genotyped to assess the association with liver function.Results: Genotype frequencies of GRIA1 rs4958351, CNOT3 rs73062673, and NFATC2 rs6021191 were higher/lower than previously reported. One hundred and forty-four patients were included in the association analysis of which, 18 (12.5%) developed L-ASP hypersensitivity. Though the frequency of hypersensitivity was higher in patients that carried the risk alleles of the three investigated genes, no statistically significant differences were observed. Association analysis between PNPLA3 rs738409 and liver function could not be investigated due to a lack of clinical information.Conclusion: In conclusion, none of the tested genes did predict L-asparaginase hypersensitivity in an Ethiopian pediatric ALL patients.Keywords: acute lymphoblastic leukemia, L-asparaginase, hypersensitivity